(untitled) (Philological Studies, 2019)
Grounded in the constructionist approach to language, as principally represented in works by Goldberg (1996) and Jackendoff (2010), this article examines some important features of the so-called light verb constructions (Butt 2003). Following a short overview of certain observations made by various theoreticians, ranging from those aligned with contemporary Anglo-American schools of linguistic thought (GradečakErdeljić & Brdar 2012, Wittenberg et al. 2014) to those belonging to the South Slavic structuralist tradition (Radovanović 1990, Silić & Pranjković 2005), the present paper proceeds to provide a preliminary analysis of a selection of results obtained through a psycholinguistic experiment on Croatian light verb constructions. Confronted with a formal written elicitation task, a total of 60 subjects, all of whom were speakers of Croatian, were, inter alia, asked to a) match, if deemed possible, a series of light verb constructions (as well as a series of filler constructions) with their monolexemic verbal counterparts b) to rate the degree of equivalence between the matched units and c) to rate them on scale of abstractness and concreteness. The data presented is accompanied by a short discussion and is intended to serve as the basis for subsequent practical and theoretical research on light verb constructions.